The Influence of Service Quality, Customer Satisfaction, and Customer Loyalty on WOM in E-commerce: A Case Study of Local Fashion Products - Alanbachtiar Rizky Suwandhi; Unik Dwi Lestari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Along with technological developments, shopping via e-commerce is increasingly popular with the public. This is because it is more practical and also provides competitive prices. This research aims to determine the influence of service quality, customer satisfaction, and customer loyalty to generate WOM in local fashion products that use e-commerce. The population in this research is local fashion product customers who make purchases using e-commerce and live in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas, with a sample of 270 respondents. The data collection technique was carried out using a Likert scale questionnaire which was distributed online via Google Form. The sampling technique in this research used purposive sampling. Analysis uses the Structural Equation Modeling (SEM) method with Partial Least Square (PLS). The research results show that service quality has a positive effect on customer satisfaction, customer loyalty and WOM. This research provides managerial implications for the management of local fashion product companies in JABODETABEK that sell via e- commerce in terms of increasing the positive WOM of their customers by improving service quality. This study can be developed by conducting research in other locations or for other products and can also add other variables that influence customers' positive WOM.